The Mediating Effect of Sleep Disturbance on the Relationship Between Nonmalignant Chronic Pain and Suicide Death. Issue 4 (18th January 2019) - Owen‐Smith, Ashli A.; Ahmedani, Brian K.; Peterson, Ed; Simon, Gregory E.; Rossom, Rebecca C.; Lynch, Frances L.; Lu, Christine Y.; Waitzfelder, Beth E.; Beck, Arne; DeBar, Lynn L.; Sanon, Victoria; Maaz, Yousef; et al.
Abstract: Importance: Few studies have examined the relationship between nonmalignant chronic pain (NMCP) and suicide death, and even fewer have specifically explored what role sleep disturbance might play in the association between NMCP and suicide death. Objective: To assess whether sleep disturbance mediates the relationship between NMCP and suicide death. Design: This case‐control study included 2, 674 individuals who died by suicide between 2000 and 2013 (cases) and 267, 400 matched individuals (controls). Setting: Eight Mental Health Research Network (MHRN)‐affiliated healthcare systems. Participants: All cases and matched controls were health plan members for at least 10 months during the year prior to the index date. Main Outcomes and Measures: Sociodemographic data and diagnosis codes for NMCP and sleep disorders were extracted from the MHRN's Virtual Data Warehouse. Suicide mortality was identified using International Statistical Classification of Diseases and Related Health Problems (ICD)‐10 codes from official government mortality records matched to health system records. Results: After accounting for covariates, there was a significant relationship between NMCP and sleep disturbance; those who were diagnosed with NMCP were more likely to develop subsequent sleep disturbance. Similarly, sleep disturbance was significantly associated with suicide death. Finally, a significant indirect effect of NMCP on suicide death, through sleep disturbance, and a nonsignificant direct effect of NMCP on suicide death provide support for a fully mediated model. Conclusions and Relevance: There is a need for clinicians to screen for both sleep disturbance and suicidal ideation in NMCP patients and for health systems to implement more widespread behavioral treatments that address comorbid sleep problems and NMCP.